Frihedscensur. Teleovervågning i det befriede Danmark, 1945 - Nielsen, Jacob Vrist (Fra Krig og Fred, 2026)
During the German occupation of Denmark millions of private telephone conversations and telegrams were monitored. But on the day of liberation, May 5, 1945, the censorship was closed. Denmark was free at last. Nonetheless, a week later the censorship restarted. 2e Allied Powers had negotiated with the Danish ministries about reinstating the surveillance, and the new Danish Government had accepted an o0er of “voluntarily censorship”. Officials from Denmark had to conduct the mass surveillance but under British and American supervision. Inspired by modern theories of “normalizing the exceptional” and “surveillance creep” and with Denmark as a case study, this article presents the first analysis of the postwar surveillance in Denmark, and it explores the entangled and contested relationship between security, surveillance, and citizen rights in times of crisis. Officially, the surveillance was a relaxation of wartime censorship rules. However, drawing on confidential primary source material the article argues that the postwar surveillance was an intensification of the wartime surveillance. The article demonstrates that the Danish Ministry of Justice and the judicial experts specified that the surveillance was illegal and unconstitutional, but the Danish Government chose not to pass the required laws. Additionally, the article shows that once the surveillance was established, it expanded rapidly and started serving predominantly Danish interests.